2016
DOI: 10.2522/ptj.20140522
|View full text |Cite
|
Sign up to set email alerts
|

Sitting and Activity Time in People With Stroke

Abstract: Participants with stroke spent more time sitting and less time in activity than their age-matched peers. Further work is needed to determine whether reducing sitting time is feasible and leads to clinically important reductions in cardiovascular risk in this population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
122
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 160 publications
(136 citation statements)
references
References 46 publications
5
122
0
1
Order By: Relevance
“…Previous studies have shown that people with chronic stroke spend a large proportion of their waking hours sitting each day 26 and around half of all sitting time is accumulated in bouts greater than 30 minutes 26 . The relationship between increased daily sitting time (especially prolonged sitting time) and risk of cardiovascular disease, diabetes and early mortality is well documented 27 .…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that people with chronic stroke spend a large proportion of their waking hours sitting each day 26 and around half of all sitting time is accumulated in bouts greater than 30 minutes 26 . The relationship between increased daily sitting time (especially prolonged sitting time) and risk of cardiovascular disease, diabetes and early mortality is well documented 27 .…”
Section: Discussionmentioning
confidence: 99%
“…It is well known that persons with stroke are less active compared to healthy peers, with around half the daily step count and fitness levels well below the average for their age [5, 6]. Low aerobic capacity has been shown after acquired brain injury (ABI) as well [7].…”
Section: Introductionmentioning
confidence: 99%
“…However, achieving sufficient PA levels for persons with stroke or ABI has proven difficult [9]. Understanding why persons with stroke or ABI are less active than their healthy peers is vital if they are to be supported to meet the recommended levels of PA [5, 8]. Already at an early stage, it is crucial that we understand the barriers and motivators to PA after stroke or ABI [10, 11].…”
Section: Introductionmentioning
confidence: 99%
“…Despite the evidence in support of exercise and physical activity in adult neurologic populations, exercise uptake is not consistent 11,24,25 and is limited by significant barriers. 2628 These include individual safety and fear of falling, low outcome expectation from exercise, lack of time to exercise, and the location at which exercising takes place.…”
Section: Health Promotion and Secondary Prevention In Adult Neurologimentioning
confidence: 99%